2022
DOI: 10.1111/1750-3841.16152
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella spp. in low water activity food: Occurrence, survival mechanisms, and thermoresistance

Abstract: The occurrence of disease outbreaks involving low‐water‐activity (aw) foods has gained increased prominence due in part to the fact that reducing free water in these foods is normally a measure that controls the growth and multiplication of pathogenic microorganisms. Salmonella, one of the main bacteria involved in these outbreaks, represents a major public health problem worldwide and in Brazil, which highlights the importance of good manufacturing and handling practices for food quality. The virulence of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 190 publications
1
6
0
Order By: Relevance
“…In food industry, desiccation and hyperosmotic treatments for effective inhibition of the growth of microorganisms are the most common methods of food preservation. However, it has been widely reported that Salmonella can survive desiccation for long periods under low water activity conditions (Dhaliwal et al, 2021;Morasi et al, 2022). Consistent with the previous work, Salmonella in this study remained stable population during the dehydration treatment and SMP storage, which indicated that Salmonella had developed adaptability to low moisture conditions.…”
Section: Measurement Of Key Enzyme Activities and Atp Contentsupporting
confidence: 91%
See 1 more Smart Citation
“…In food industry, desiccation and hyperosmotic treatments for effective inhibition of the growth of microorganisms are the most common methods of food preservation. However, it has been widely reported that Salmonella can survive desiccation for long periods under low water activity conditions (Dhaliwal et al, 2021;Morasi et al, 2022). Consistent with the previous work, Salmonella in this study remained stable population during the dehydration treatment and SMP storage, which indicated that Salmonella had developed adaptability to low moisture conditions.…”
Section: Measurement Of Key Enzyme Activities and Atp Contentsupporting
confidence: 91%
“…However, during the storage in SMP, Salmonella activated long-term adaptive responses by regulating more kinds of metabolites, such as amino acids, nucleic acids, fatty acids, carbohydrates, inorganic salts, organic acids, peptides, lipids, and others. This illustrated that complicated regulation mechanisms of Salmonella were present during its adaptation in LMFs (Morasi et al, 2022). A detailed profiling of all DEMs obtained from the aforementioned between-group comparisons for all three groups (i.e., the 0-, 24 h, and 3-month samples) was shown in Supplementary Figure 6, which exhibited clear changes of metabolite pattern in either the desiccation group or the storage group when compared with the 0-samples.…”
Section: Identification Of Significant Differentially Expressed Metab...mentioning
confidence: 93%
“…These biofilms may be persisting and be surviving for years on the food processing surface (Bourdichon et al., 2021). In recent years there has been an increase in recalls and outbreaks linked with LMFs, such as condiments, chocolates, dry dairy, dry infant foods, dried meats, flour, honey cereal, seeds, sesame seed‐based products, nuts and nut butters, peanuts, peanut butter, and almonds (Bourdichon et al., 2021; Hertwig et al., 2022; Morasi et al., 2022).…”
Section: Pathogens Associated With Biofilm Formation In Lmf Manufactu...mentioning
confidence: 99%
“…Several studies have shown that Salmonella has the ability to tolerate desiccation stress, allowing it to survive in LMFs and their processing environments for lengthy periods of time [ 5 , 6 , 7 ]. Furthermore, Salmonella cells subjected to dry conditions become more heat-tolerant [ 7 ].…”
Section: Introductionmentioning
confidence: 99%